Use of hand signals for communication during dental procedure - R Vignesh; T Sukanya; Indra Priyadharshni (Wolters Kluwer Medknow Publications, 2016)
Introduction: Fear of dental treatment and anxiety about dental procedures are highly prevalent and have an impact on the quality of dental treatment. Use of a means of communication during the treatment procedure, which is the crucial point of communication, is not much studied. Aim: The aim of this study was to assess the perception of patients and practices of dentists regarding the usage of hand signals during dental procedure. Materials and Methods: A cross-sectional questionnaire study was conducted among 150 outpatients attending a dental institute and 150 dental practitioners practicing in North Chennai. The questionnaire constituted five questions based on difficulty in communication and attitude toward hand-sign usage. The data were subjected to Pearson's Chi-square statistical analysis. Results: About 76.7% (n = 115) of the respondents felt uncomfortable to communicate with dental practitioner when there is instrument in the mouth. About 66% (n = 99) of the respondents experienced fear, when they were unable to express their pain with instruments in their mouth during any dental procedure. Among the respondents, 71.3% (n = 107) agreed that using hand signals during a dental treatment might help them to overcome the difficulty in communication. About 30% (n = 45) of the dental practitioners preferred patients to talk, 54% (n = 81) preferred use of hand signals, and 16% (n = 24) preferred making sounds. About 63.3% (n = 95) of the dental practitioners informed their patients to raise their hand as a signal to stop the procedure. Conclusion: Majority of the practitioners and patients prefer the usage of hand signals over other means of communication to reduce fear and anxiety and improve rapport.